ALI JUM'AH SUFISTIC THINKING AND ITS RELEVANCE ON ISLAMIC EDUCATION (PAI) IN HIGHER EDUCATION - Fahrudin Fahrudin; M. Abdul Somad; Risris Hari Nugraha; Muhamad Parhan; Mohammad Rindu Fajar Islamy (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2021)
Abstract:Strengthening spiritual values through the dimensions of tasawwuf learning is one of the efforts to improve changes in students' moral mentality. Sheikh Ali Jum'ah as a charismatic cleric at Al-Azhar University and a former Mufi of Egypt, one of the international scholars who payed attention to the discourse, according to him, instilling modern Sufistic values of Sufism in the young generation can be a supporter of forming a young age who is religious and has good intellect. This article aims to examine and explore the Sufistic concept of Alī Jum'ah to increase individual piety and discuss the relevance of its Sufistic theory to the learning of Islamic Religious Education in Higher Education. Using a literature review approach, his works are collected from various sources and studied interactively through the Islamic studies approach. The primary reference source is his work entitled At-Tharīq Ilā Allah, while the second reference refers to other books. The Sufistic concept of Alī Jum'ah is built on six main principles where the axis is Allah Al-Makshd Al-Kulli. At the practical level, repentance, tafakkur, tadabbur, and consistency in dhikr are the primary tools for ma'rifatullah. Manhaj, the existence of a Murshid and a Salik are the essential pillars in the world of Sufism. Its sufistic relevances in PAI learning which substantially impacts on strengthening the five main components, namely learning objectives, learning materials, learning approaches, lecturers, and students in higher education.Abstrak: Memperkuat nilai-nilai spiritualitas melalui dimensi pembelajaran tasawwuf merupakan salah satu upaya untuk memperbaiki perubahan mentalitas akhlak pada siswa. Syeikh Ali Jum’ah sebagai ulama kharismatik Universitas Al-Azhar dan manfat Mufi Mesir salah satu ulama internasional yang menaruh perhatian terhadap diskurus tersebut dimana menurutnya menanamkan nilai-nilai sufistik tasawwuf modern terhadap generasi muda dapat menjadi penyokong membentuk generasi muda yang religius serta memiliki intelektualitas baik. Artikel ini bertujuan untuk menelaah serta menjelajahi konsep sufistik Alī Jum’ah dalam rangka meningkatkan kesalehan individu serta mengkaji relevansi teori sufistiknya terhadap pembelajaran Pendidikan Agama Islam di Perguruan Tinggi. Dengan menggunakan pendekatan literature review, karya-karya beliau dikumpulkan dari berbagai sumber serta dianalisis secara interaktif melalui pendekatan Islamic studies. Sumber rujukan primer diambil dari karyanya berjudul At-Tharīq Ilā Allah sedangkan rujukan sekunder merujuk kepada kitab-kitab yang lainnya. Konsep Sufistik Alī Jum’ah dibangun atas enam kaidah utama dimana porosnya adalah Allah Al-Makshūd Al-Kulli. Tataran praktisnya, aktivitas taubat, tafakkur, tadabbur, dan konsistensi dalam dzikir menjadi alat utama menuju ma’rifatullah. Manhaj, keberadaan Mursyid dan Seorang Salik merupakan rukun-rukun esensial dalam dunia tasawwuf. Relevansi sufistiknya dalam pembelajaran PAI berdampak kuat terhadap penguatan empat komponen utama yaitu tujuan pembelajaran, metode pembelajaran, dosen, serta mahasiswa di perguruan tinggi.